Scientific Opinion on the substantiation of a health claim related to glycaemic carbohydrates and contribution to normal cognitive function pursuant to Article 13(5) of Regulation (EC) No 1924/2006. (25th February 2015) - ,; ,
Abstract: Following an application from Dextro Energy GmbH & Co. KG, submitted for the authorisation of a health claim pursuant to Article 13(5) of Regulation (EC) No 1924/2006 via the Competent Authority of Germany, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to glycaemic carbohydrates and contribution to normal cognitive function. The scope of the application was proposed to fall under a health claim based on newly developed scientific evidence. The Panel considers that the food constituent, glycaemic carbohydrates, which is the subject of the health claim, is sufficiently characterised in relation to the claimed effect. Contribution to normal cognitive function is a beneficial physiological effect. Glycaemic carbohydrates contribute to the maintenance of normal brain functions, including cognition. The Panel concludes that a cause and effect relationship has been established between the consumption of glycaemic carbohydrates and contribution to normal cognitive function. A daily intake of 130 g of glycaemic carbohydrates has been estimated to cover the glucose requirement of the brain. Such amounts can be consumed as part of a balanced diet. The target population is the general population.